GC × GC-ToF-MS and GC-IMS based volatile profile characterization of the Chinese dry-cured hams from different regions. (April 2021) - Li, Wenqian; Chen, Yan Ping; Blank, Imre; Li, Fuyang; Li, Chunbao; Liu, Yuan
Graphical abstract: Highlights: GC × GC-ToF-MS and GC-IMS results both are suitable for product clustering by statistical analysis. GC-IMS is a good choice to discriminate dry-cured hams from different regions. PCA and MFA can distinguish six Chinese hams on the basis of GC × GC-ToF-MS and GC-IMS data. Xuanen ham having smoky aroma is significantly distinct from other hams. Abstract: Chinese dry-cured hams have unique aroma characteristics appreciated by local consumers. The volatile organic compounds (VOCs) of six selected Chinese dry-cured hams ( Mianning, Nuodeng, Saba, Sanchuan, Wanhua, and Xuanen ) were analyzed by solvent assisted flavor evaporation (SAFE) combined with GC × GC-ToF-MS and head-space (HS) injection combined with GC-IMS. To visualize VOCs and differentiate samples, principal component analysis (PCA) and multiple factor analysis (MFA) were performed. GC × GC-ToF-MS resulted in over five times more VOCs (265) than GC-IMS (45). However, PCA and MFA indicated similar results using GC-IMS or GC × GC-ToF-MS data, suggesting HS-GC-IMS as a good choice to differentiate dry-cured hams from different regions. Xuanen ham from Yunnan Province having smoky aroma was significantly different from other hams, likely due to its unique process. Many aldehydes (heptanal, nonanal, etc.) played an important role in Sanchuan ham . Ketones were related to other four dry-cured hams, though they came from different regions. This study provides valuable analytical data to characterize and discriminate the flavor profile of Chinese dry-cured hams.